Testing the efficacy of sustainable development for the quality of governance and environmental degradation in Nigeria - Felix Aberu (International Journal of Management, Economics and Social Sciences (IJMESS), 2023)
The puzzle of identifying the determinant of sustainable development in Nigeria has become a question for research, hence, there is a need to determine these unclear a priori expectations and their impacts on the sustainable development process in Nigeria. This study used a comprehensive set of data spanning from the 1996 to 2022 extracted the World Bank database to investigate the sustainable development puzzles in Nigeria with a particular focus on establishing an empirical credence through the governance-environmental degradation hypothesis which will inform an insight into the doubtful relations of the subject matter. The ARDL cointegration estimation technique was adopted to analyze the data. The study found that sustainable development was impeded by poor governance and environmental degradation in Nigeria. Furthermore, findings also show that environmental degradation has a crowd-out relationship from the one-period lag to the fourth-period lag values, while one-period lag to three-period lag values of governance have a negative and significant impact on sustainable development at a 5 percent level of significance, respectively. That is, development in Nigeria essentially depends on the impacts of the previous environment and the quality of governance influences. Hence, short-term policy objectives should be fostered in maintaining the conditions for sustainable development through good governance and a more sustained environment.
Keywords: E01; G30; Q01; 330; Sustainable development; governance; environmentaldegradation ARDL; Nigeria